Evaluation and implementation of behavioral and educational tools that improves the patients' intentional and unintentional non-ad - Abdulla Shehab; Asim Ahmed Elnour; Shirina Al Swaidi; Akshaya Srikanth Bhagavathula; Farah Hamad; Omar Shehab; Mahmoud AbuMandil; AboBakr Abasaeed; Ahmed Dahab; Naama Al Kalbani; Rouda Abdulla; Sahar Asim; et al. (Elsevier, 2016)
Objective: There are limited number of studies describing the reasons and interventions of non-adherence to cardiovascular medications in United Arab Emirates (UAE). We aimed to implement and evaluate the behavioral and educational tools that indicate the reasons of non-adherence in patients with cardiovascular diseases and improve patient's adherence to their cardiovascular medications. Methods: In this prospective interventional study, we recruited patients (n = 300) with cardiovascular diseases from three family medicine clinics in Al Ain, UAE in 2010. We assessed patients' responses to a validated brief medication questionnaire (BMQ). Results: At the end of the study, we observed a significant improvement in adherence. When we compared pre- and post-interventions, the mean (± standard deviation, SD) score for non-adherence to current regimen were 4.1 ± 0.2 vs. 3.0 ± 0.3 (p = 0.034); indication of negative believes or motivational barriers scores was 1.8 ± 0.4 vs. 0.9 ± 0.1 (p = 0.027); the indication of recall barrier scores was 1.6 ± 0.1 vs. 0.8 ± 0.1 (p = 0.014); and the indication of access barrier scores was 1.6 ± 0.2 vs. 0.7 ± 0.2 (p = 0.019). Mean blood pressure, fasting blood glucose, glycosylated hemoglobin, low density lipoprotein and postprandial blood glucose decreased significantly (p < 0.01) post-intervention. Conclusion: We reported that implemented multifaceted tools targeting patients, provider and healthcare system have improved the adherence to cardiovascular medications. Our interventions managed to improve patients' clinical outcome via improving adherence to prescribed cardiovascular medications.